Slovenska in evropska pravna določila varstva in obnove rečnih koridorjev - Bizjak, Aleš (Urbani izziv, 2003)
In view of the state of hydromorphological preservation of river corridors in the Slovenian hydrographic network and because of demands imposed by domestic and European legislature concerning water resource management and environmental protection, certain sections of rivers and streams that were forvarious reasons regulated in the past, will have to be rehabilitated. Permanent solutions to such issues demand careful planning of rehabilitation on suitable sections of rivers and streams, adequate positioning within physical planning acts, as well as streamlined administrative procedures and devised maintenance of rehabilitation areas. Because the process demands the return of formerly taken water surfaces into the domain of water ecosystems and dynamics of hydromorphological processes, and consequentially maintenance of regained surfaces, the public becomes an important factor, which is a position, granted by domestic and European laws. Last, but not least, successful execution of rehabilitation of water corridors, besides planning, administration and consistent public participation, demands knowledge about good practices of project management, as well as technical execution of such projects.
Keywords: ecology; ekologija; hidrologija; obnova; površinske vode; pravna ureditev; prostorsko urejanje; rečne struge; varstvo voda; vodotoki